An unexpected consensus among diverse ways to measure democracy. Issue 5 (4th July 2022) - Baltz, Samuel; Vasselai, Fabricio; Hicken, Allen
ABSTRACT: We show that behind decades of disagreements over how to classify regime types, there is an unexpectedly strong consensus about which countries have been democratic in which years. We match many-valued classifications of democracies and autocracies to binary classifications, by finding the cutpoint that dichotomizes each many-valued measure so that it matches each binary measure as closely as possible. Despite the sharp differences between these datasets, we find identical or nearly identical optimal cutpoints for almost every major classification. This is evidence of a strong underlying agreement between the classifications. We show that the many-valued measures, when dichotomized in the optimal way, can replicate major results in the study of democracy. We also examine which sorts of countries are counted as democracies in this consensus, and we show that countries where national elections have never produced a turnover between parties are a particular focus of disagreement.